2006
DOI: 10.1152/japplphysiol.00818.2005
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for using accelerometer data to predict energy expenditure

Abstract: The purpose of this study was to develop a new two-regression model relating Actigraph activity counts to energy expenditure over a wide range of physical activities. Forty-eight participants [age 35 yr (11.4)] performed various activities chosen to represent sedentary, light, moderate, and vigorous intensities. Eighteen activities were split into three routines with each routine being performed by 20 individuals, for a total of 60 tests. Forty-five tests were randomly selected for the development of the new e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
384
3
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(403 citation statements)
references
References 17 publications
11
384
3
5
Order By: Relevance
“…The underestimate of PAL by the accelerometer may in part be due to the underestimation of accelerometer counts for the various moderate to vigorous-intensity activities observed in our study. Similar problems have been reported for this accelerometer (formerly Computer Science and Application Inc.) and for other accelerometers as well (26)(27)(28) . In contrast, the mean PAL from the questionnaire compared well with that obtained with the 24 h AD although 24 h AD is prone to over-reporting as it relies on self-report (29) .…”
Section: Discussionsupporting
confidence: 83%
“…The underestimate of PAL by the accelerometer may in part be due to the underestimation of accelerometer counts for the various moderate to vigorous-intensity activities observed in our study. Similar problems have been reported for this accelerometer (formerly Computer Science and Application Inc.) and for other accelerometers as well (26)(27)(28) . In contrast, the mean PAL from the questionnaire compared well with that obtained with the 24 h AD although 24 h AD is prone to over-reporting as it relies on self-report (29) .…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, in line with previous research (20), a relatively high cut point of Ͻ100 counts/min was chosen for sedentary time. Although it is unlikely to change the direction of the findings, a lower cut point for sedentary time may be more appropriate, given the recent evidence that nonambulatory standing activities, such as the filing of paperwork, can register a quite low average of 60 counts/ min (28). Also, there is some evidence that the relationship between accelerometer counts and physical activity intensity varies across individuals (29).…”
Section: -Associations Of 2-h Plasma Glucose With Quartiles Of Percenmentioning
confidence: 99%
“…Also, there is some evidence that the relationship between accelerometer counts and physical activity intensity varies across individuals (29). Future research, using shorter epoch lengths, should utilize recently published regression equations that more accurately capture free-living physical activity (28).…”
Section: -Associations Of 2-h Plasma Glucose With Quartiles Of Percenmentioning
confidence: 99%
“…Laboratory tests have shown that prediction equations developed during ambulatory activities were not adequate to describe the relationship between activity counts and the metabolic cost of sedentary and lifestyle-related activities. 62,63 Considering that accelerometers should be able to describe the energy cost of any type of activity performed in daily life, validations in free-living conditions have also been done by comparing measurements of activity counts to doubly-labeled water. Recent reviews 26,35 reported that not all accelerometers can accurately estimate AEE in free-living conditions, and subjects' characteristics are often the only significant contributors to the explained variance in AEE of the prediction models.…”
Section: Activity Energy Expenditure Estimation Using Accelerometersmentioning
confidence: 99%
“…Firstly, more complex modeling techniques have been used to estimate energy expenditure from accelerometer data. Crouter et al 63 proposed to predict energy expenditure using a two-regression equation model based on activity counts measured in epochs of 10 s. Rothney et al 68 developed an artificial neural network to process the raw acceleration signal measured during a 24-h stay in a respiration chamber to improve energy expenditure estimations.…”
Section: Improvements In Energy Expenditure Estimationmentioning
confidence: 99%